Numerical Analysis of Structural Coloration of Dark Color Pearls by Nacre Crystal Multilayers - Asai, Masamitsu; Wakabayashi, Hideaki; Yamakita, Jiro (Journal of Advanced Simulation in Science and Engineering, 2025)
The structural coloration of pearls is due to optical multilayer interference by nacre. This paper considers the structural coloration of dark color pearls by nacre consisting of a multilayer of conchiolin and aragonite crystals. The Maxwell’s equations in 4×4 matrix form which use a relative permittivity tensor are introduced and solved. Calculating the reflection spectrum and the chromatic coordinates in standard red-green-blue (sRGB) color space, the effects of orientation of the c-axis on the structural coloration are investigated and shown.